Demografisk struktur i landsbyen Tirup - Boldsen, Jesper (Hikuin, 2000)
Demographic structure in the village of Tirup By Jesper Boldsen The people of Tirup are by far the best known medieval population in the world. This knowledge is not founded on an exceptionally large sample of skeletons or written documentation but on the analyses that the total excavation of the cemetery has facilitated. The Tirup skeletons have been published in many different, mostly international journals and no comprehensive summary of recent research into this population is available. The present paper attempts to compensate this a little. The Tirup cemetery was in use during a critical phase of the history of the European population. It covers a period of rapid change of the mortality pattern – the demographic transition from the Peasant Ages to the Early Modern Period. This period and thus the Tirup population was characterised by an extreme level of age independent mortality most clearly visible in the high ration of older to younger pre-adult mortality. The high level of pre-adult mortality forced fertility to its natural maximum, and as most of the children who did not make it to adulthood died after weaning, the reproductive burden on the women exceeded the level seen in any other period. The result was a substantial female surplus mortality in the reproductive ages. The effect of these difficult living conditions is reflected by the sharp decline in population size in the whole of Western and Northern Europe during the 14th century.